UTILIZATION OF MEDICINAL PLANTS FOR HEALTH IN CINUNUK VILLAGE, BANYURESMI SUB-DISTRICT, GARUT DISTRICT - Diah Wardani, Diah Wardani; Taufik Huda, Taufik Huda; Nurul, Nurul (Jurnal Pengabdian Masyarakat DEDIKASI, 2023)
During this time, the use of traditional medicinal plants is only based on theopinions of parents, relatives, friends or neighbors. The use of traditional medicine that is not in accordance with the rules is feared to reduce theefficacy of the medicine itself. If the use is too much, it is feared that it will also have a toxic effect that will endanger the community. This activity aims to provide knowledge to residents about the benefits of medicinal plants. The method used in this community service is counseling and health education with a total of 50 participants. The results obtained in this activity are an increase of 34% of residents who understand the benefits of medicinal plants and residents who understand the benefits of medicinal plants after counseling as many as 42 people or 84% so that the implementation of community service activities is considered effective and acceptable to the community. The conclusion obtained from this activity is that medicinal plants are very beneficial for health and need to be empowered in residents in Cinunuk Village, Banyuresmi, Garut.